SYSTEMATIC ANALYSIS OF THE DOMINANT TYPES OF ENTOMOPHAGES IN FRUIT ORCHARDS - М.К. Раkhmanova; К.Q. Khamdamov; U. Rasulova; G. Turdiyeva,; G. Rahmonova; R. Saliyeva (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
The    formation      of        entomophauna         in        orchards        and            their  development has a great importance, and it greatly influences to the number of phitofags. During our observations of entomophages orchard in agrobiocenosis  indentified  24 dominant types which belong to seven families. Moveover, researches of entomophages show 24 dominant types which belong to 7 families. Besides that we have analysed the share of entomophage varieties concerning the entomophages